An approach to the study of foundlings in Seville at the end of the 16th century and the first half of the 17th century through the analysis of baptism books - Pérez González, Silvia María; Arias Pérez, Baltasar (Cuadernos de Historia Moderna, 2021)
This article aims to study the foundlings of Seville at the end of the 16th century and the first half of the 17th century. In this regard, it is intended to be a contribution to the panorama of Spanish charity in relation to abandoned children during the Early Modern Period, a panorama which, despite still manifesting certain imbalances, has been enormously enriched by new studies approached from multi-institutional perspectives. The documentary base on which it is based consists of 5,600 items contributed by the baptismal books kept in the parish of La Magdalena. Therefore, its main objectives are to study the situation of the foundlings in terms of annual figures of abandoned children, percentages by sex, names, family and spiritual ties based on the figures of the godparents, as well as the response of the Church and religion to this phenomenon.